Microwave hydrothermal synthesis of WO3(H2O)0.333/CdS nanocomposites for efficient visible-light photocatalytic hydrogen evolution - Ma, Tingting; Li, Zhen; Liu, Wen; Chen, Jiaxu; Wu, Moucui; Wang, Zhenghua (Frontiers of materials science, 2021)
WO 3 (H 2 O) 0.333 /CdS (WS) nanocomposites are obtained via a rapid microwave hydrothermal method, and they are served as visible light-driven photocatalysts for the H 2 generation. By using Pt as the cocatalyst, the WS nanocomposite with 70 wt.% CdS reaches the H 2 evolution rate of 10.32 mmol·g −1 ·h −1 , much quicker than those of WO 3 (H 2 O) 0.333 and CdS. The cycling test reveals the good photocatalytic stability of the WS nanocomposite. The carrier transfer mechanism of WS nanocomposites can be explained by the Z-scheme mechanism. The existence of the Z-scheme heterojunction greatly helps to separate photogenerated carriers and thus improves the photocatalytic activity. The present work provides a rapid synthesis method for preparing Z-scheme heterojunction photocatalysts, and may be helpful for the green production of hydrogen.